Hierarchical Mechanisms for Direct Reprogramming of Fibroblasts to Neurons - Wapinski, Orly L.; Vierbuchen, Thomas; Qu, Kun; Lee, Qian Yi; Chanda, Soham; Fuentes, Daniel R.; Giresi, Paul G.; Ng, Yi Han; Marro, Samuele; Neff, Norma F.; Drechsel, Daniela; Martynoga, Ben; et al. (Cell, 2013)
Direct lineage reprogramming is a promising approach for human disease modeling and regenerative medicine, with poorly understood mechanisms. Here, we reveal a hierarchical mechanism in the direct conversion of fibroblasts into induced neuronal (iN) cells mediated by the transcription factors Ascl1, Brn2, and Myt1l. Ascl1 acts as an “on-target” pioneer factor by immediately occupying most cognate genomic sites in fibroblasts. In contrast, Brn2 and Myt1l do not access fibroblast chromatin productively on their own; instead, Ascl1 recruits Brn2 to Ascl1 sites genome wide. A unique trivalent chromatin signature in the host cells predicts the permissiveness for Ascl1 pioneering activity among different cell types. Finally, we identified Zfp238 as a key Ascl1 target gene that can partially substitute for Ascl1 during iN cell reprogramming. Thus, a precise match between pioneer factors and the chromatin context at key target genes is determinative for transdifferentiation to neurons and likely other cell types. [Display omitted] •Ascl1 has pioneer activity, accessing closed chromatin to allow other factors to bind•Unlike other pioneer factors, Ascl1 binds its physiologic neural targets in fibroblasts•A trivalent chromatin domain predicts iN reprogramming ability in other cell types•Zfp238 is a direct Ascl1 target and critical mediator of iN cell reprogramming Of three transcription factors that together convert different cell types into induced neuronal (iN) cells, Ascl1 leads the way as the “pioneer factor,” followed by Brn2 and Myt1l. A trivalent chromatin state at Ascl1 target genes predicts which types of cells will respond to reprogramming by these factors.